Unique Tube–Ring Interactions: Complexation of Single‐Walled Carbon Nanotubes with Cycloparaphenyleneacetylenes. Issue 26 (21st May 2018) - Miki, Koji; Saiki, Kenzo; Umeyama, Tomokazu; Baek, Jinseok; Noda, Takeru; Imahori, Hiroshi; Sato, Yuta; Suenaga, Kazu; Ohe, Kouichi
Abstract: Carbon nanotubes (CNTs) interlocked by cyclic compounds through supramolecular interaction are promising rotaxane‐like materials applicable as 2D and 3D networks of nanowires and disease‐specific theranostic agents having multifunctionalities. Supramolecular complexation of CNTs with cyclic compounds in a "ring toss'' manner is a straightforward method to prepare interlocked CNTs; however, to date, this has not been reported on. Here, the "ring toss" method to prepare interlocked CNTs by using π‐conjugated carbon nanorings: [8]‐, [9]‐, and [10]cycloparaphenyleneacetylene (CPPA) is reported. CPPAs efficiently interact with CNTs to form CNT@CPPA complexes, while uncomplexed CPPAs can be recovered without decomposition. CNTs, which tightly fit in the cavities of CPPAs through convex–concave interaction, efficiently afford "tube‐in‐ring"‐type CNT@CPPA complexes. "Tube‐in‐ring"‐type and "ring‐on‐tube"‐type complexation modes are successfully distinguished by spectroscopic, thermogravimetric, and microscopic analyses. Abstract : "Ring toss" : Carbon nanotubes (CNTs), which tightly fit in the cavities of π‐conjugated carbon nanorings, [8]‐, [9]‐, and [10]cycloparaphenyleneacetylenes (CPPAs), through convex–concave interaction, efficiently afford "tube‐in‐ring"‐type CNT@CPPA complexes.